Preparation and Physical and Photocatalytic Activity of a New Niobate Oxide Material Containing NbO4 Tetrahedra - Hengkai Pan; Bei Wang; Feng Zhang; Weifeng Zhang; Guoqiang Li (International Journal of Photoenergy)
The shape and connection type of MOx are critical to the physical and chemical properties. A series of new material Sr2-xNaxNbO4 containing NbO4 tetrahedra was prepared by controlling the ratio of SrCO3 to sodium niobate under ambient air. With increasing the content of Sr in the sample, the MOx shape will change from NbO6 octahedra to NbO4 tetrahedra, which is confirmed by the Raman scattering spectra. With increasing the content of NbO4 in the sample, the lattice parameter increases, optical band gap becomes larger, and the surface changes to be more active for oxygen adsorption, resulting in a higher photocatalytic activity.